DIFFERENCES IN THE LEVEL OF BASIC AND SPECIFIC MOTOR ABILITIES IN NINE-YEAR-OLD GIRLS TREATED WITH ELEMENTS OF RHYTHMIC GYMNASTICS - Jadranka Kocić; Slađana Milošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The elements of rhythmic gymnastics, taking the variety of movements, props for exercises and musical accompaniment which is obligatory during exercises into account, give huge possibilities in terms of versatile motor development. The research was conducted with the aim to determine the status of basic and specific motor abilities in 47 nine-year-old (+/- 6 months) girls, third-grade students of elementary school in Nis. The experimental treatment lasted for 12 weeks and it consisted of elements of rhythmic gymnastics. Before the begining and after the end of the experimental treatment, the initial and final measurement were conducted, and they consisted of 25 motor tests. The gained results were processed by the method of canonical discriminative analysis and they are shown in tables and descriptively. By the usage of canonical discriminative analysis in motor and specific motor space, one discriminative function, which maximally separates different measurements according to the coefficient, was isolated. The girls were separated according to their mobility (spreading legs side lying by left and right), repetitive strength (modified BURPE-test in 20 seconds), balance (position on one leg with their eyes closed) and tests of coordination (polygon backwards and side steps). After three months of experimental treatment, it can be concluded that generally, it did not come to the statistically significant influence on quantitative and qualitative changes. Such gained results show that rhythmic gymnastics belongs to the group of very complex aesthetic-coordination sports in which training and sports preparation imply long-term work with subsequently visible effects. Because of the specific demands in terms of conduction of specific motor movements, it is also necessary to possess a high degree of development of basic motor abilities. Significant differences were gained in balance tests, and partial differences in tests of mobility, repetitive strength and coordination.